2013
DOI: 10.1002/jsfa.6370
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sensorial, phytochemical and biological properties of new isotonic beverages enriched with lemon and berries during shelf life

Abstract: All the studied parameters remained quite stable during preservation, in general, and the new isotonic drinks can be useful to equilibrate redox balance in acute and intense exercise, and support weight loss programmes, avoiding triglyceride absorption and hyperglycaemia involved in obesity and diabetes mellitus, respectively. Further research in vivo is necessary to verify their beneficial effects for sports, nutrition and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 41 publications
(70 reference statements)
6
54
0
6
Order By: Relevance
“…Water/formic acid (99:1, v/v) (solvent A) and acetonitrile/formic acid (99:1, v/v) (solvent B) were used for chromatographic separation in an Agilent HPLC 1100 series equipped with a photodiode array detector and a mass detector in series (Agilent Technologies, Waldbronn, Germany) with the same conditions described by Gironés-Vilaplana, Mena, Moreno, and García-Viguera (2013). Briefly, the flow rate was 1 mL min − 1 using the linear gradient scheme (t in min; %B): (0; 5%), (15; 15%), (30; 30%), (40; 50%), (45, 95%), and (50; 5%).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Water/formic acid (99:1, v/v) (solvent A) and acetonitrile/formic acid (99:1, v/v) (solvent B) were used for chromatographic separation in an Agilent HPLC 1100 series equipped with a photodiode array detector and a mass detector in series (Agilent Technologies, Waldbronn, Germany) with the same conditions described by Gironés-Vilaplana, Mena, Moreno, and García-Viguera (2013). Briefly, the flow rate was 1 mL min − 1 using the linear gradient scheme (t in min; %B): (0; 5%), (15; 15%), (30; 30%), (40; 50%), (45, 95%), and (50; 5%).…”
Section: Plant Materialsmentioning
confidence: 99%
“…En este caso, el contenido de polifenoles totales para ambos jugos (con azúcar y sin azúcar de maqui) son elevados (Tabla 1) en comparación con otros jugos como el jugo de maqui y limón que contienen entre 62,97 a 243,64 mg EAG 100 mL -1 (Gironés-Vilaplana et al, 2012a) y mezclas isotónicas de maqui, que muestran altos contenidos de fenoles totales por el método de Folin-Ciocalteu con valores de 80,97 mg 100 mL -1 de ácido gálico (Gironés-Vilaplana et al, 2014). Según Ramírez et al (2009) un producto con un elevado contenido de polifenoles de origen vegetal, es un producto saludable y considerado como alimento funcional.…”
Section: Polifenoles Totalesunclassified
“…Por lo tanto, la elaboración de nuevas bebidas alimenticias con alto valor nutricional que promueven la salud, como el jugo de maqui, es factible de producir (Gironés-Vilaplana et al, 2012b) y utilizar como suplemento nutricional o medicinal (Rubilar et al, 2011), con atractivo color y buenos atributos sensoriales (Gironés-Vilaplana et al, 2014).…”
Section: Carbohidratos Totalesunclassified
“…Similarly, Schreckinger et al [32] identified seven anthocyanins in which cyanidin-3,5-diglucoside was not included. Gironés-Vilaplana et al [33,34] also identified cyanidin-3-glucoside-5-rhamnoside in maqui fruit. Fredes et al [35] evaluated the anthocyanin contents of 18 maqui genotypes during two growing seasons in which two genotypes (from the same geographical area) had cy-3-sa and del-3-sa at trace levels.…”
Section: Maqui Fruitsmentioning
confidence: 96%
“…Recently, maqui anthocyanins have been used in the design of new beverages [30,33] and isotonic drinks [34,57] with lemon juice and maqui as a potential functional and/or healthy beverage. In these beverages, lyophilised maqui fruit is added to lemon juice at levels of 2 and 5%.…”
Section: New Research On Maqui: the Powerful Colour Of Maqui Fruitmentioning
confidence: 99%